2015
DOI: 10.1589/jpts.27.3315
|View full text |Cite
|
Sign up to set email alerts
|

Action observation for upper limb function after stroke: evidence-based review of randomized controlled trials

Abstract: [Purpose] The purpose of this study was to suggest evidenced information about action observation to improve upper limb function after stroke. [Methods] A systematic review of randomized controlled trials involving adults aged 18 years or over and including descriptions of action observation for improving upper limb function was undertaken. Electronic databases were searched, including MEDLINE, CINAHL, and PEDro (the Physiotherapy Evidence Database), for articles published between 2000 to 2014. Following compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Elisabetta S et al [ 56 ] reviewed 20 randomized controlled trials (from or before 1982 to 2015) and found the beneficial effect of AO therapy on motor training including dexterity in subacute stroke. Kim K et al [ 10 ] conducted another review of randomized controlled trials (from 2000 to 2014) in which all included studies demonstrated significant improvement in motor function with AO therapy except a study by Cowles T et al [ 7 ], which did not show significant effect of AO therapy, which could be because they trained participants without videos. Incongruent movements between execution and observation also could not demonstrate better effect like that of congruent movements [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elisabetta S et al [ 56 ] reviewed 20 randomized controlled trials (from or before 1982 to 2015) and found the beneficial effect of AO therapy on motor training including dexterity in subacute stroke. Kim K et al [ 10 ] conducted another review of randomized controlled trials (from 2000 to 2014) in which all included studies demonstrated significant improvement in motor function with AO therapy except a study by Cowles T et al [ 7 ], which did not show significant effect of AO therapy, which could be because they trained participants without videos. Incongruent movements between execution and observation also could not demonstrate better effect like that of congruent movements [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even mild UE impairments after stroke significantly limit daily activities and negatively impact quality of life [ 5 ]. Evidence shows increasing attention to mirror neuron system-based interventions for functional training in stroke [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For both clinical conditions, the majority of the studies reported a clear beneit of AOT, with a maintained improvement in the motor condition and the functional status. In fact, the beneit of this therapy has been remarked on in a recent evidenced-based review of the literature concerning the efect of AOT in upper limb dysfunction after stroke [21].…”
Section: Neurological Physical Therapymentioning
confidence: 97%
“…7 Recently, some studies have reported on the potential benefits of mental practice and action observation training, for promoting motor skill acquisition, as an adjunct to physical training in patients with brain lesions such as stroke. 811…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, some studies have reported on the potential benefits of mental practice and action observation training, for promoting motor skill acquisition, as an adjunct to physical training in patients with brain lesions such as stroke. [8][9][10][11] A lack of walking competency in the community is strongly related to an impaired cognitive process, 12 which makes it difficult to establish attention and executive function in different community environments; this process can be facilitated by using action observation training. 10 Since the point of action observation is to observe another subject performing an action, it leads to recruitment in the same brain region as actual physical practice; moreover, it may reflect the same plastic cortical representation in the motor system as the actual performance of motor action, 10 possibly through the mirror neuron system.…”
Section: Introductionmentioning
confidence: 99%